2000
DOI: 10.1067/mhn.2000.105470
|View full text |Cite
|
Sign up to set email alerts
|

Comparative External Versus Endoscopic Dacryocystorhinostomy: Results in 115 Patients (130 Eyes)

Abstract: Hammer-chisel endoscopic DCR is practical, less traumatic, less time-consuming, and cosmetically more convenient than the external approach. The success rate of the endoscopic DCR procedure is comparable with that of traditional external DCR, and it also allows simultaneous correction of any intranasal pathology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
124
1
9

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 196 publications
(142 citation statements)
references
References 22 publications
8
124
1
9
Order By: Relevance
“…Similar intraoperative complication rate was seen in the study conducted by Cokkeser et al in which intraoperative haemorrhage occured in 15% eyes during external DCR and 15.69% eyes during endonasal DCR. (23) Duwal and Saiju in their study reported intraoperative bleeding in 5.88% patients of endoscopic DCR and 6.45% patients of endoscopic DCR. (18) Our results are comparable to Gauba who reported 18% cases of intraoperative haemorrhage in external DCR and 13% cases of intraoperative haemorrhage in endonasal DCR.…”
Section: Discussionmentioning
confidence: 99%
“…Similar intraoperative complication rate was seen in the study conducted by Cokkeser et al in which intraoperative haemorrhage occured in 15% eyes during external DCR and 15.69% eyes during endonasal DCR. (23) Duwal and Saiju in their study reported intraoperative bleeding in 5.88% patients of endoscopic DCR and 6.45% patients of endoscopic DCR. (18) Our results are comparable to Gauba who reported 18% cases of intraoperative haemorrhage in external DCR and 13% cases of intraoperative haemorrhage in endonasal DCR.…”
Section: Discussionmentioning
confidence: 99%
“…Cokkeser et al 3 , comparing DCR EX to DCR EN in 115 patients had success rates of 89.8% and 88.2%, respectively, and recommend the use of endonasal techniques owing to their advantages comparing to the external approach. The success of the endonasal technique in our service was 82.3%, similarly to the results reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Cokkerser et al 3 , Sham et al 12 , Wormald et al 13 consider that the removal of the whole bone from the sac is associated with better index of success and visualization of opening of common canaliculi, after the removal of the media wall of the sac, which is a good indicator of appropriate saccular exposure 11 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations